The Therapeutic Effect of Homologous and Heterologous Antitoxins in Experimental Diphtheria and Tetanus - Smith, J. W. G. (1970)
Antitoxic sera against diphtheria and tetanus toxins were prepared in mice, guinea-pigs, rabbits and monkeys. The therapeutic effect of the antitoxins was compared in mice injected subcutaneously with tetanus toxin and in guinea-pigs injected intracutaneously with diphtheria toxin. The comparisons were made by varying the time interval between the injection of constant doses of toxin and antitoxin. Homologous antitoxin was not found to have any superiority over heterologous antitoxin in controlling the effects of the toxin injections. It is suggested that when used therapeutically the dose of homologous antitoxin should be the same as that of heterologous antitoxin.